Hello! my name is Tasty : global diner favorites from Portland's Tasty restaurants - Gorham, John (Chef); Crain, Liz (Sasquatch Books, 2017)
This collection of recipes from the Tasty restaurants in Portland take you through the day, from brunch through cocktails. The recipes are designed to give a good yield so that you have plenty to share, and also to experiment with. Gorham and Crain also provide tips for variations, encouraging you to experiment with the recipes so that they will become your own kitchen staples.